A Preliminary Design of a Hybrid Machine for Additive and Subtractive Manufacturing - Nanang Ali Sutisna (Journal of Mechanical Engineering and Mechatronics, 2020)
Additive manufacturing (AM) or commonly called 3D printing (3DP) and rapid prototyping (RP) is a  technique of blending materials by either fusion, binding, or solidifying materials. Despite many advantages of AM, there is a drawback  of AM such as the surface quality may not be as good as subtractive machining  (SM) process, therefore it will be better to have the initial shape forming process with AM and then finishing the required surface with SM process within a single setup. This paper presents the preliminary design of hybrid AM-SM machine to process a resin based material. The design includes structural design and control design of the machine using the material and firmware widely available in the market. Keyword: Additive, Subtractive,  Manufacturing,  Hybrid  Machine